Factors that Influence Students in the Use of E-Wallet DANA in the Spending Payment System - Dian (Penerbit Hellow Pustaka, 2024)
With the growing and sophisticated technology of the current technology supported by Pandemi Covid-19, people are accustomed to utilizing technology to help daily activities, one of which is in terms of payments commonly called digital wallets or e-wallet. Therefore, this study aims to find out, analyze and explain the factors that influence consumer interest in using e-wallet, especially UINSU students. The research used is descriptive data processing, namely recording the results of interviews or observations supported by secondary data, and qualitative analysis through analysis of 10 respondents. The results of this study found that comfort, safety, promotion, features, new technology experiences, and promotions have a positive and significant effect on the interest in the use of digital wallets among students.